Genotype by environment interactions for growth in Red Angus - Fennewald, D. J.; Weaber, Robert L.; Lamberson, W. R. (My University, 2017)
Accuracy of sire selection is limited by how well animals are characterized for their environment. The objective of this study was to evaluate the presence of genotype x environment interactions (GxE) for birth weight (BiW) and weaning weight (WW) for Red Angus in the United States. Adjusted weights were provided by the Red Angus Association of America. Environments were defined as 9 regions within the continental United States with similar temperature-humidity indices. Mean weights of calves were determined for each region and for each sire's progeny within each region. A reaction norm (RN) for each bull was estimated by regressing the sire means on the region means weighted for the number of progeny of each sire. The range for BiW and WW RN was -1.3 to 4.0 and -1.7 to 2.8, respectively. The heritabilities of BiW and WW RN were 0.40 and 0.39, respectively. Phenotypic and genetic correlations between BiW and WW RN were 0.19 and 0.54, respectively. The phenotypic correlation of the progeny mean to the RN was -0.20 (P < 0.05) and suggests that sires with higher means are more stable in progeny performance across environments. Weights in different regions were considered separate traits and genetic correlations were estimated between all pairs of regions as another method to determine GxE. Genetic correlations < 0.80 indicate GxE at a level for concern, but existed for only 2 of 36 estimates for BiW and 12 of 36 estimates for WW. Genetic correlations between different regions ranged from 0.74 to 0.96 for BiW and 0.62 to 0.99 for WW and indicate that sires tend to rank similarly across environments for these traits.
Citation: Fennewald, D. J., Weaber, R. L., & Lamberson, W. R. (2017). Genotype by environment interactions for growth in Red Angus. Journal of Animal Science, 95(2), 538-544. doi:10.2527/jas2016.0846
Keywords: Beef Cattle; Genotype X Environment Interaction; Growth; Reaction Norms; Red Angus; Hereford Cattle